Rhamnose Is Superior to Mannitol as a Monosaccharide in the Dual Sugar Absorption Test: A Prospective Randomized Study in Children With Treatment-Naïve Celiac Disease - Holtz, Lori R.; Hoffmann, Julie; Linneman, Laura; He, Mai; Smyrk, Thomas C.; Liu, Ta-Chiang; Shaikh, Nurmohammad; Rodriguez, Cynthia; Dyer, Roy B.; Singh, Ravinder J.; Faubion, William A. (Frontiers in Pediatrics, 2022)
Background and Aim: We sought to correlate two different measures of gut permeability (lactulose:mannitol (L:M) and lactulose:rhamnose (L:R)) to the severity of duodenal histopathology in children with and without elevated antibodies to tissue transglutaminase (tTG). A secondary objective was to correlate gut permeability with celiac disease (CD) serology and indices of inflammation and bacterial product translocation. Methods: We prospectively randomized children undergoing endoscopy with abnormal (n=54) and normal (n=10) concentrations of circulating antibodies to tTG, to either L:M or L:R. Biopsies underwent modified Marsh scoring to measure mucosal injury. Circulating anticore E. coli lipopolysaccharide (LPS) IgG, α-1 acid glycoprotein, LPS-binding protein, and C-reactive protein concentrations were measured by enzyme immunoassays. Results: Of the 54 cases with positive celiac serology, 31% and 69% had modified Marsh 0/1 scores or 3a, respectively. Circulating tTG IgA correlated with the modified Marsh score (p=0.03). L:R, but not L:M or percent L excreted, differed according to modified Marsh scores (p=0.01). There was no significant association between any systemic marker of inflammation or gut injury, and modified Marsh scores. Concerningly, most participants had evidence of urinary M before the challenge sugar was administered. Conclusions: L:R, but not L:M, is associated with modified Marsh scores in children undergoing small bowel biopsy for suspected CD. Despite increased intestinal permeability, we see scant evidence of systemic exposure to gut microbes in these children. Gut permeability testing with L:R may predict which patients with abnormal celiac serology will have biopsy evidence for celiac disease and reduce the proportion of such patients undergoing endoscopy whose Marsh scores are  1. M should not be used as a monosaccharide for permeability testing in children.